2011
DOI: 10.1007/s11033-011-1226-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of intra-population variability of Jatropha curcas L. using DNA based molecular markers

Abstract: Jatropha curcas L. (Euphorbiaceae) has acquired a great importance as a renewable source of energy with a number of environmental benefits. Very few attempts were made to understand the extent of genetic diversity of J. curcas germplasm. In the present study, efforts were made to analyze the genetic diversity among the elite germplasms of J. curcas, selected on the basis of their performance in field using random amplified polymorphic DNA (RAPD), amplified fragment length polymorphism (AFLP) and simple sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 15 publications
0
12
1
7
Order By: Relevance
“…The genetic diversity found in the present study was greater than that reported in studies conducted in China (Shen et al, 2010), Malaysia (Sun et al, 2008), India (Mastan et al, 2012), Taiwan (Mavuso et al, 2016), Thailand (Sirisak et al, 2015), and even studies conducted in other germplasm banks in Brazil (Rosado et al, 2010;Grativol et al, 2011;LiraMedeiro et al, 2013;Alves et al, 2013). The genetic diversity among groups analyzed by the Nei's index (1987) was significantly higher (0.12) than that found among Chinese accessions (0.19) as reported by Cai et al (2010).…”
Section: Discussioncontrasting
confidence: 94%
“…The genetic diversity found in the present study was greater than that reported in studies conducted in China (Shen et al, 2010), Malaysia (Sun et al, 2008), India (Mastan et al, 2012), Taiwan (Mavuso et al, 2016), Thailand (Sirisak et al, 2015), and even studies conducted in other germplasm banks in Brazil (Rosado et al, 2010;Grativol et al, 2011;LiraMedeiro et al, 2013;Alves et al, 2013). The genetic diversity among groups analyzed by the Nei's index (1987) was significantly higher (0.12) than that found among Chinese accessions (0.19) as reported by Cai et al (2010).…”
Section: Discussioncontrasting
confidence: 94%
“…Genetic improvement may alleviate this problem; however, characterization of the available germplasm is needed for breeding programs to be efficient (King et al, 2015; Mastan et al, 2012). Over the past decade, J. curcas germplasm has been genetically evaluated in India, China, Brazil, Mexico, Costa Rica and Central America (Avendaño et al, 2015; Basha & Sujatha, 2007; China Plant BOL Group et al, 2011; Montes Osorio et al, 2014; Pecina-Quintero et al, 2014; Rosado et al, 2010; Wen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Lower percentage of polymorphism was obtained by He et al (2007) and Cai et al (2010) using ISSR; however, it was higher than that reported by Machua et al (2011), of 55.33%, using RAPD. Additional information was reported by Mastan et al (2012), who obtained polymorphism of 56.43, 57.9, and 36.84, using RAPD, AFLP, and SSR, respectively. The optimum number of loci for the obtainment of genetic estimation accuracy is 103 polymorphic fragments for a stress of 0.0097, and the optimum correlation (r) is 0.9962.…”
Section: Resultsmentioning
confidence: 99%